Test–Retest Repeatability of the Pupil Light Response to Blue and Red Light Stimuli in Normal Human Eyes Using a Novel Pupillometer - Herbst, Kristina; Sander, Birgit; Milea, Dan; Lund-Andersen, Henrik; Kawasaki, Aki (Frontiers in Neurology, 2011)
In this study, we evaluated the repeatability of pupil responses to colored light stimuli in healthy subjects using a prototype chromatic pupillometer. One eye of 10 healthy subjects was tested twice in the same day using monochromatic light exposure at 2 selected wavelengths (660 nm and 470 nm, intensity 300 cd/m2) presented continuously for 20 seconds. Pupil responses were recorded in real time before, during and after light exposure. Maximal contraction amplitude and sustained contraction amplitude were calculated. In addition, we quantified the summed pupil response during continuous light stimulation as the total area between a reference line representing baseline pupil size and the line representing actual pupil size over 20 seconds (area under the curve). There was no significant difference in the repeated measure compared to the first test for any of the pupil response parameters. In conclusion, we have developed a novel prototype of color pupillometer which demonstrates good repeatability in evoking and recording the pupillary response to a bright blue and red light stimulus.